2015
DOI: 10.28930/jitkt.v6i2.9022
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Silicate in Coastal Water of South Sulawesi

Abstract: Dissolved silicate (DSi) Keywords: dissolved silicate, diatom, chlorophyll-a, coastal waters, South Sulawesi ABSTRAKSilikat terlarut di perairan pesisir dan laut berperan penting dalam pertumbuhan fitoplankton seperti diatom. Penelitian ini bertujuan untuk menghitung konsentrasi silikat terlarut di perairan pesisir pantai barat Sulawesi Selatan pada musim yang berbeda, dan untuk melihat hubungannya dengan kepadatan diatom dan klorofil-a. Sampel air, klorofil, dan plankton dikumpulkan pada April 2013 (musim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
2
0
4
Order By: Relevance
“…High inputs of N, primarily in the form of NH + 4 , and SPM, which carries a high proportion of particulate organic matter (POM), is discharged from the mouth of the Tallo River into the nearshore coastal area of Spermonde Archipelago (Nasir et al, 2015(Nasir et al, , 2016. Chl a concentrations at the river mouth have been found to be as high as 2-7 mg m −3 (Lukman et al, 2014;Nasir et al, 2015), which supports the relatively high concentrations we observed in 2012 at 1 km from the coast. The change in magnitude of Chl a concentrations over seasons and across years serves as a good indicator of current nutrient availability status, despite the low levels of inorganic nutrients found in the water-column.…”
Section: Evidence Of a Cross-shelf Gradient Of Water Quality In Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…High inputs of N, primarily in the form of NH + 4 , and SPM, which carries a high proportion of particulate organic matter (POM), is discharged from the mouth of the Tallo River into the nearshore coastal area of Spermonde Archipelago (Nasir et al, 2015(Nasir et al, , 2016. Chl a concentrations at the river mouth have been found to be as high as 2-7 mg m −3 (Lukman et al, 2014;Nasir et al, 2015), which supports the relatively high concentrations we observed in 2012 at 1 km from the coast. The change in magnitude of Chl a concentrations over seasons and across years serves as a good indicator of current nutrient availability status, despite the low levels of inorganic nutrients found in the water-column.…”
Section: Evidence Of a Cross-shelf Gradient Of Water Quality In Spermmentioning
confidence: 99%
“…Effluents originating from the city have been shown to affect the archipelago to varying degrees. Nearshore islands (up to 7 km offshore) are exposed to regular sediments, aquaculture outflow and wastewater from fluvial discharge of the nearby rivers, while midshelf reefs (7-27 km offshore) are impacted by effluents during the onset of the rainy season during the northwestern monsoon (Moll, 1983;Renema and Troelstra, 2001;Lukman et al, 2014;Nasir et al, 2015Nasir et al, , 2016. Finally, offshore islands (>27 km) are rarely exposed to high levels of terrestrial effluents from the mainland.…”
Section: Introductionmentioning
confidence: 99%
“…Konsentrasi silikat terlarut yang tinggi di Stasiun 2 tak terlepas dari sumber nutrien yang berada di muara sungai. Sumber silikat di perairan pesisir berasal dari hasil pelapukan mineral tanah yang mengandung silika yang larut dalam aliran sungai menuju pesisir dan laut (Liu et al, 2009;Lukman et al, 2014). Selain itu, curah hujan yang tinggi menyebabkan terjadinya pengenceran pada konsentrasi silikat di perairan (Zhang et al, 2005).…”
Section: Parameter Fisika Dan Kimia Perairanunclassified
“…Stasiun 2 dicirikan oleh konsentrasi silikat baik saat pasang maupun surut. Konsentrasi silikat terlarut yang tinggi di Stasiun 2 tak terlepas dari kondisi lingkungan seperti sumber nutrien yang berada di muara sungai Geniot yang berasal dari hasil pelapukan mineral tanah yang mengandung silikat yang larut dalam aliran sungai menuju pesisir dan laut (Liu et al, 2009;Lukman et al, 2014).…”
Section: Keterkaitan Kelimpahan Diatom Dengan Parameter Fisika Kimia unclassified
“…Fenomena ini di sebagian besar perairan dunia meningkat frekuensi, intensitas dan distribusi geografis selama beberapa dekade terakhir (Blondeau-Patissier, et al, 2014) termasuk di perairan Indonesia. Pada beberapa perairan di Indonesia seperti Teluk Jakarta (Prayitno & Afdal, 2019) dan pesisir Sulawesi Selatan (Lukman et al, 2014) konsentrasi klorofil-a menunjukkan peningkatan.…”
unclassified